2004
DOI: 10.1152/jn.00527.2003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Responses of Primate Spinothalamic Tract Neurons to Pruritic and Algogenic Stimuli

Abstract: Comparison of responses of primate spinothalamic tract neurons to pruritic and algogenic stimuli. J Neurophysiol 91: 213-222, 2004; 10.1152/jn.00527.2003. We investigated the role of mechanosensitive spinothalamic tract (STT) neurons in mediating 1) the itch evoked by intradermal injection of histamine, 2) the enhanced sense of itch evoked by innocuous stroking (alloknesis), and 3) the enhanced pain evoked by punctate stimulation (hyperalgesia) of the skin surrounding the injection site. Responses to intrader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 32 publications
3
68
0
1
Order By: Relevance
“…Also consistent with these latter reports, the majority of 5-HTsensitive Vc units were presently categorized as WDR or NS, with a small percentage being mechanically insensitive. Importantly, the vast majority of 5-HT-responsive units additionally responded to the algogens AITC and capsaicin (Table 3), consistent with previous studies from our laboratory as well as studies of histamine-or cowhage-sensitive primate spinothalamic tract neurons that always also responded to capsaicin (Davidson et al 2007;Simone et al 2004).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Also consistent with these latter reports, the majority of 5-HTsensitive Vc units were presently categorized as WDR or NS, with a small percentage being mechanically insensitive. Importantly, the vast majority of 5-HT-responsive units additionally responded to the algogens AITC and capsaicin (Table 3), consistent with previous studies from our laboratory as well as studies of histamine-or cowhage-sensitive primate spinothalamic tract neurons that always also responded to capsaicin (Davidson et al 2007;Simone et al 2004).…”
Section: Discussionsupporting
confidence: 86%
“…These data support the concept of a labeled line for itch. However, the vast majority of spinal neurons that respond to cutaneous application of pruritogens such as histamine, 5-HT, or cowhage spicules (containing itch-inducing proteases; Reddy et al 2008) also responded to capsaicin and/or allyl isothiocyanate (AITC) (Akiyama et al 2009a(Akiyama et al , 2009bDavidson et al 2007;Jinks and Carstens 2002;Simone et al 2004). Behavioralgenetic studies also indicate that nociceptive neurons may be capable of signaling itch (Imamachi et al 2009;Shim et al 2007), arguing against labeled-line coding for itch versus pain.…”
mentioning
confidence: 99%
“…Neurophysiological studies in cats and monkeys have shown that thermoreceptive and nociceptive spinothalamic tract (STT) neurons in the MZ project to the ventral posterior lateral nucleus (VPL) (Willis et al, 1974;Price et al, 1978;Ferrington et al, 1987;Craig and Dostrovsky, 2001;Simone et al, 2004). However, this projection has remained unexplored in the rat.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in cats, histamine-responsive mechano-insensitive neurons were described in the dorsal horn (lamina I) of the spinal cord [25]. However, histamineresponsive spinothalamic tract neurons were also identified among the mechano-, heat-and capsaicin-sensitive ones in primates [26]. It is therefore suggested that spinal projection neurons may receive innervation from both itch sensitive and nociceptive primary fibers [13] which supports the selectivity over the specificity hypothesis regarding the relation of itch and pain transmitting pathways.…”
Section: Spinal Itch Processingmentioning
confidence: 99%